G2019S LRRK2 Mutation Enhances MPP+-Induced Inflammation of Human Induced Pluripotent Stem Cells-Differentiated Dopaminergic Neurons - Chen, Ying; Yin, Qing; Cheng, Xiao-Yu; Zhang, Jin-Ru; Jin, Hong; Li, Kai; Mao, Cheng-Jie; Wang, Fen; Bei, Hong-Zhe; Liu, Chun-Feng (Frontiers in Neuroscience, 2022)
Induced pluripotent stem cells (iPSCs) offer an unprecedented opportunity to mimic human diseases of related cell types, but it is unclear whether they can successfully mimic age-related diseases such as Parkinson’s disease (PD). We generated iPSCs lines from three patients with familial PD associated with the G2019S mutation in the LRRK2 gene and one age-matched healthy individual (control). During long-term culture, dopaminergic (DA) neurons differentiated from iPSCs of G2019S LRRK2 PD patients exhibited morphological changes, including a reduced number of neurites and neurite arborization, which were not evident in DA neurons differentiated from control iPSCs. To mimic PD pathology in vitro, we used 1-methyl-4-phenylpyridium (MPP+) to damage DA neurons and found that DA neurons differentiated from patients with G2019S LRRK2 mutation significantly reduced the survival rate and increased apoptosis compared with the controls. We also found that the mRNA level of inflammatory factors [interleukin (IL)-1β, tumor necrosis factor-α, cyclooxygenase-2, IL-6, and inducible NO synthase] with G2019S LRRK2 mutation were higher than control group after exposure to MPP+. Our study provides an in vitro model based on iPSCs that captures the patients’ genetic complexity and investigates the pathogenesis of familial PD cases in a disease-associated cell type.